Measuring and interpreting trends in the division of labour in the Netherlands - I. Semih Akçomak; Lex Borghans; Bas ter Weel (Institute for the Study of Labor (IZA), 2011)
This paper introduces indicators about the division of labour to measure and interpret recent trends in the structure of employment in the Netherlands. Changes in the division of labour occur at three different levels: the level of the individual worker, the level of the industry and the spatial level. At each level the organisation of work is determined by an equilibrium of forces that glue tasks together or unbundle them. Communication costs are the main force for clustering or gluing together tasks; comparative advantage stimulates unbundling and specialisation. The estimates suggest that on average the Netherlands has witnessed unbundling in the period 1996-2005, which implies that advantages of specialisation have increased. These developments explain to a considerable extent changes in the structure of employment. Especially at the spatial level it explains a substantial part of the increase in offshoring tasks abroad.
urn:nbn:de:101:1-201105173017
Keywords: J23; J24; O33; 330; division of labour; tasks; technological change; the Netherlands; Arbeitsteilung; Unternehmensentflechtung; Offshoring; Niederlande